PENDIDIKAN KARAKTER: STRATEGI PENDIDIKAN NILAI DALAM MEMBENTUK KARAKTER RELIGIUS - Heri Cahyono (Pascasarjana IAIN Metro, 2016)
This research aimed to know the educational strategy value in constructing the students’ religious character. This research used descriptive analytic that used the scholars’ theories about the value of education in constructing of character building. As for the researcher conducted analysis in roder to know the effectiveness of educational strategy value which is considered ineducation world. The finding of this research concluded that the educational strategy value can use several strategies, that are moral knowing, modeling and moral modeling, feeling and loving the good, moral acting, punihsment, admonition, and habituation. As for the success of constructing the students’ character is when the people has multi-competence as well as the science of moral knowing, moral feeling and moral action as a the entity which is can not be separated.